Proceedings of the 4th ACM/IEEE International Conference on Human Robot Interaction 2009
DOI: 10.1145/1514095.1514158
|View full text |Cite
|
Sign up to set email alerts
|

How anthropomorphism affects empathy toward robots

Abstract: A long-standing question within the robotics community is about the degree of human-likeness robots ought to have when interacting with humans. We explore an unexamined aspect of this problem: how people empathize with robots along the anthropomorphic spectrum. We conducted an experiment that measured how people empathized with robots shown to be experiencing mistreatment by humans. Our results indicate that people empathize more strongly with more human-looking robots and less with mechanicallooking robots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
167
5
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 235 publications
(186 citation statements)
references
References 7 publications
(6 reference statements)
11
167
5
3
Order By: Relevance
“…Second, using humanlike primitives for controlling robotic systems could improve the effectiveness and safety of human-robot interaction (HRI). Indeed, several studies identified anthropomorphism as one of the key enabling factor for successful, acceptable, predictable, and safe HRI in many fields, such as human robot co-working and rehabilitative/assistive robotics (Duffy, 2003;Bartneck et al, 2009;Riek et al, 2009;Dragan and Srinivasa, 2014). Furthermore, the here reported experimental and analytical framework could be used to identify principal actuation schemes for under-actuated robotic devices.…”
Section: Conclusion and Implications For Robotics And Bioengineeringmentioning
confidence: 87%
“…Second, using humanlike primitives for controlling robotic systems could improve the effectiveness and safety of human-robot interaction (HRI). Indeed, several studies identified anthropomorphism as one of the key enabling factor for successful, acceptable, predictable, and safe HRI in many fields, such as human robot co-working and rehabilitative/assistive robotics (Duffy, 2003;Bartneck et al, 2009;Riek et al, 2009;Dragan and Srinivasa, 2014). Furthermore, the here reported experimental and analytical framework could be used to identify principal actuation schemes for under-actuated robotic devices.…”
Section: Conclusion and Implications For Robotics And Bioengineeringmentioning
confidence: 87%
“…It has been shown that individuals show more empathy toward more anthropomorphic robots (Riek et al, 2009;Darling, 2015). Convincing simulation of humanlike hand and eye movements may induce implicit impressions of animacy and anthropomorphism, potentially attributing greater value and pleasure to robotic art through empathic responses (Bartneck et al, 2009).…”
Section: The Importance Of Embodiment In Artmentioning
confidence: 99%
“…In our previous work, we sought to understand how people could empathize with robots of varying degrees of humanlikeness [12], [13]. However, as we discovered during the course of our research, this problem is multi-faceted.…”
Section: Introductionmentioning
confidence: 99%